Creative expression and its relationship to reflective thinking skills The students of the fourth literary grade, Karbala, have a model - a theoretical study (Journal of the College of Basic Education, 2022)
Creative expression and contemplative thinking are two of the most important goals that societies strive to instill in their children, and after conducting numerous literary and scientific studies on the subject, The researchers discovered that middle school students' creative expression suffers from a strong decline in linguistic and creative output. They concluded that the deficiency in the levels of creative expression stems from shortcomings reflected by the lack of a systematic approach that relies on solid metrics to evaluate these skills and methods that Taking these abilities into consideration. taking into consideration the cognitive mental processes involved in reasoning and imagination As a result, creative expression is nothing more than a set of constructive processes, whether in form or content, that are the result of various contemplative and creative thinking styles. We can see the relationship between scientific thought and creative expression through (written) expression, and both are related to the experiences that a person has in his life, and both are related to the experiences that a person has in his life, if contemplative speech aids students in performing study and interpretation of the outcomes that they obtain through meditation in They write stories or short papers on paper, as well as introducing their observations to colleagues for review if they are unsure about them. If contemplative speech assists students in conducting research and understanding the effects of their meditation, They write stories or short articles on paper, and if they are unsure about their conclusions, they present them to colleagues for review.